Determination of Agarwood volatile compounds from selected Aquilaria species plantation extracted by Headspace-Solid Phase Microextraction (HS-SPME) method - Jalil, Abdul Majid; Abdul Hamid, Hazandy; Md. Tahir, Paridah; Mohamad Ali, Nor Azah; Jamil, Mailina; Saidin, Saidatul Husni; Lias, Sahrim (IOP Publishing, 2018)
A collection of inoculated heartwood of three Aquilaria species namely A. crassna, A. sinensis and A. subintegra were investigated for their volatile compounds. The volatile compounds were extracted using automated Headspace-Solid Phase Microextraction (HS-SPME) with fibre coating of 50/30 µm divinyl benzene/carboxen/poly-dimethylsiloxane (DVB/CAR/PDMS) and determined by gas chromatography/mass spectrometry (GCMS). The absence of proper scientific method in forming the agarwood has resulted in variations in agarwood quality and inconsistent grades in the market. Thus there is a need to quantify the amount of major volatile compounds found in the agarwood so that the quality can be scientifically verified. In this study, the commonly known volatile compounds present in agarwood sample were found but with varying amounts. At least three important compounds were obtained i.e. β-agarofuran, α-eudesmol and agarospirol. Based on the presence of these main volatile compounds, the study suggests that extraction by HS-SPME also useful instead of distillation process. The ability to identify key components in a short time can facilitate and shorten the analysis time. It further helps in developing the quality of agarwood industry standards.